OPPORTUNITY TO LEARN SCIENCE TOGETHER WITH JAPANESE STUDENTS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 24 October 2015 –The students of SMK (P) St. George and Penang Free School were presented with a rare opportunity of learning science together with the students of Yokohama Science Frontier High School (YSFHS), Japan at the Chancellory Conference Hall, Universiti Sains Malaysia (USM) recently.